NON-ENGLISH STUDENTS’ STRATEGIES IN IMPROVING THEIR SPEAKING SKILLS - Riska Azisah; Rezki Awalia; Ardiana; Ishmah Afifah (IKIP Siliwangi, 2024)
The importance of speaking skills in learning English has prompted this research to explore the strategies applied by non-English students. In this context, this research aims to explore the strategies used by non-English students to improve their speaking skills in English. Using a qualitative approach, this research involved in-depth interviews as a data collection method. The instrument used in this research was an interview guide. The interview guide was prepared based on the research objective, namely to find out what strategies non-English students use to improve their speaking skills. A total of 10 non-English-majoring students from various departments were selected at university Muhammadiyah of Makassar as research subjects. From the results of the interviews conducted, there were two strategies used by students to improve their speaking skills, namely: internal strategies and external strategies. Internal strategies include: self-speaking practice, committing to memorizing vocabulary every day, shadowing technique, read news articles in English, language switching strategies and determining speaking time. Meanwhile, the external strategy includes: getting used to communicating with family and friends using English (a natural communication strategy); taking an English course, forming a friendship circle. Knowing the students’ strategies in enhancing their speaking skills, teachers can integrate them into their learning in the speaking classroom.